Manuscripts of fourteenth century English polyphony: facsimiles - Harrison, Frank Llewellyn; Wibberley, Roger (London Stainer and Bell, 1981)
This handsome volume of 212 plates is an important work of reference for all concerned with the notation of early music. Major sources represented include those of the British Library, the Bodleian Library Oxford, and the University of Cambridge.